1999
DOI: 10.1007/pl00011751
|View full text |Cite
|
Sign up to set email alerts
|

The Benefit of a Roseobacter Species on the Survival of Scallop Larvae

Abstract: : A marine strain (BS107), identified as a Roseobacter species, was antagonistic to Vibrio species on agar plates. Results suggested that the inhibitory effect was displayed only in the presence of another bacterium. Quantification of the antibacterial activity showed that 48-hour-coculture supernatants from BS107 and another bacterial strain (V. anguillarum 408) reached the highest titers of bacterial inhibition. The antibacterial substance was also liberated when supernatants from V. anguillarum 408 were add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
91
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(97 citation statements)
references
References 20 publications
3
91
1
2
Order By: Relevance
“…However, most of them, with the possible exception of the Oceanospirillales species, could not establish stable colonizing populations in the early steps of surface community development, in contrast to the surfacecolonizing Rhodobacterales species. It has been found that certain Roseobacter clade bacteria produce antibacterial compounds when they are growing on a surface, preventing other bacteria, including ␥-Proteobacteria, from colonizing the surface and forming a biofilm (8,10,11,24,44,48). A strain was even found to invade and disperse preestablished biofilms formed by other bacteria (45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most of them, with the possible exception of the Oceanospirillales species, could not establish stable colonizing populations in the early steps of surface community development, in contrast to the surfacecolonizing Rhodobacterales species. It has been found that certain Roseobacter clade bacteria produce antibacterial compounds when they are growing on a surface, preventing other bacteria, including ␥-Proteobacteria, from colonizing the surface and forming a biofilm (8,10,11,24,44,48). A strain was even found to invade and disperse preestablished biofilms formed by other bacteria (45).…”
Section: Discussionmentioning
confidence: 99%
“…Once the Roseobacter clade bacterial populations reach a certain density, they may actively expel or take advantage of the other surface-attaching bacteria via quorum-sensing-regulated antibiotic production and other mechanisms (8,10,11,24,35,44,45,48,57). Quorum sensing may also be important for multispecies biofilm formation (22,35,58).…”
Section: Discussionmentioning
confidence: 99%
“…(cepa 11) en el control de infecciones causadas por V. anguillarum en cultivos larvarios del pectínido Argopecten purpuratus. Ruiz-Ponte et al (1999) mejoraron la supervivencia larvaria de Pecten maximus cuando se usa una mezcla de Roseobacter sp. (Cepa BS107) y V. anguillarum (cepa 408).…”
Section: Discussionunclassified
“…Varios estudios con probióticos han mostrado un control sobre infecciones generadas por V. tubiashii en larvas de C. gigas (Gibson et al 1998), la inhibición de Vibrio sp. en larvas de P. maximus (Ruiz-Ponte et al 1999) y A. purpuratus (Riquelme et al 2000), además de la mejora en la supervivencia, el crecimiento y la resistencia a enfermedades en Haliotis midae (Macey & Coyne 2005).…”
unclassified
“…An alternative to antibiotics in such systems is probiotics, that is live microorganisms which exert beneficial effects on the host health (FAO and WHO, 2001), for example by inhibiting growth of pathogenic bacteria (Gatesoupe, 1999; Skjermo and Vadstein, 1999; Kesarcodi‐Watson et al ., 2008). Members of the genera Phaeobacter and Ruegeria which produce the broad‐spectrum antimicrobial compound tropodithietic acid (TDA) have proven probiotic properties (Ruiz‐Ponte et al ., 1999; Hjelm et al ., 2004; Planas et al ., 2006; D'Alvise et al ., 2012). Phaeobacter spp.…”
Section: Introductionmentioning
confidence: 99%